Organizations of personal significance in adolescents according to the postrationalist model of Vittorio Guidano - Meza, Marta (2022)
Objective: the work analyzes the Organizations of Personal Meaning (OSP) according to the postrationalistmodel of Guidano, in adolescents. Methodology: quantitative approach, encompassinga descriptive, cross-sectional, comparative and correlational study. The sample corresponded to thetotal number of students from the first to the fourth year of secondary education and the instrument ofEvaluation of Relationships of Personal Meaning (OSP) was used, which describes OSP: depressive,dápic, phobic and obsessive. Results: 36.4% of the studied sample has an obsessive OSP tendency.Following this, 33.9% have a phobic OSP trend. The t-test showed differences according to gender indepressive OSP (p = 0.007) and dpic OSP (p = 0.041). Conclusion: OSP as a dynamic construct allowthe analysis of attachment processes within the secondary community and within family ties.